2018
DOI: 10.2166/wpt.2018.001
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater quality assessment and its suitability for agricultural purposes in the Behbahan Plain, SW Iran

Abstract: Groundwater is the main agricultural water resource in arid and semi-arid regions, so, preserving it is extremely important. In this study, groundwater quality was assessed for irrigation, using the principal chemical and physical quality parameters from 30 wells in the study area. Groundwater classification on the basis of electrical conductivity reveals that more than 85% of the samples taken fall into the 'unsuitable' and 'doubtful' classes. On the basis of Richards's classification, 67% of the samples are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The RSBC values are lower than 5 mEq/L, which implies that the risk of sodium carbonate salt accumulation in the soil is low, indicating little hazardous effect of alkalinity on irrigation water quality. Thereby, the streamwater in the study area is safe for irrigational usage (Durov 1948;Ehya & Marbouti 2018). Based on the PI values, 99% of the streamwater samples from WS-1 and WS-2 fall in the excellent category while only 1% fall in the good category, showing the suitability of the streamwater for irrigational usage (Table 3).…”
Section: Suitability For Irrigationmentioning
confidence: 94%
See 1 more Smart Citation
“…The RSBC values are lower than 5 mEq/L, which implies that the risk of sodium carbonate salt accumulation in the soil is low, indicating little hazardous effect of alkalinity on irrigation water quality. Thereby, the streamwater in the study area is safe for irrigational usage (Durov 1948;Ehya & Marbouti 2018). Based on the PI values, 99% of the streamwater samples from WS-1 and WS-2 fall in the excellent category while only 1% fall in the good category, showing the suitability of the streamwater for irrigational usage (Table 3).…”
Section: Suitability For Irrigationmentioning
confidence: 94%
“…Irrigation waters with high concentrations of CO 3 À and HCO 3 À have high pH values and make soil infertile due to sodium carbonate deposition (Ehya & Marbouti 2018). As the concentrations of CO 3 À and HCO 3 À increase, so does the potential sodium hazard because of the tendency of Ca and Mg ions to precipitate as carbonates increase which in turn will increase Na in solution.…”
Section: Residual Sodium Bicarbonate (Rsbc)mentioning
confidence: 99%
“…In agriculture, [104] assessed groundwater quality for irrigation, using the principal chemical and physical quality parameters from 30 wells in Behbahan Plain, SW Iran. The study reported that groundwater classification on the basis of electrical conductivity showed that more than 85% of the samples taken were either 'unsuitable' or 'doubtful' water quality.…”
Section: Related Workmentioning
confidence: 99%
“…In endorheic saline systems, this brine accumulated due to either dissolution by water (e.g. rivers) of the outcropping rocks along the hydrological basin (Ehya & Moghadam 2017) or the groundwater-rock interaction along the hydrogeological basin (Ehya & Marbouti 2018;Chen & Gui 2019). Added to these processes, in exoreic systems, saline water is accumulated mainly due to seawater contribution (Ben Smida 2016).…”
Section: Introductionmentioning
confidence: 99%